Strategy and security in the Asia Pacific - Ayson, Robert; Ball, Desmond (Allen & Unwin, 2007)
From the impact of the 9/11 terrorist attacks to the implications of the rise of China, this book unlocks the major strategic themes and security challenges of the early 21st century. It provides the analytical frameworks students need to make sense of this complex but exciting strategic universe.